Biodiversity and agricultural sustainagility: from assessment to adaptive management - Jackson, L.; Noordwijk, Meine van; Bengtsson, J.; Foster, W.; Lipper, Leslie; Pulleman, Mirjam Margreet; Said, Mohammed Yahya; Snaddon, J.; Vodouhe, R.S. (Elsevier, 2010)
Rapid changes in land use, food systems, and livelihoods require social–ecological systems that keep multiple options open and prepare for future unpredictability. Sustainagility refers to the properties and assets of a system that sustain the ability (agility) of agents to adapt and meet their needs in new ways. In contrast, sustainability tends to invoke persistence along current trajectories, and the resilience to return to current baselines. With three examples, the use and conservation of agrobiodiversity is explored along temporal, spatial, and human institutional scales for its role in sustainagility: first, farmers’ seed systems; second, complex pollination systems; and third, wildlife conservation in agricultural areas with high poverty. Incentives are necessary if agrobiodiversity is to provide benefits to future generations.